Pentacyclic triterpenes in birch bark extract inhibit early step of herpes simplex virus type 1 replication - Navid, Mojdeh Heidary; Laszczyk‐Lauer, Melanie; Reichling, Jürgen; Schnitzler, Paul (Phytomedicine, 2014)
Antiviral agents frequently applied for treatment of herpesvirus infections include acyclovir and its derivatives. The antiviral effect of a triterpene extract of birch bark and its major pentacyclic triterpenes, i.e. betulin, lupeol and betulinic acid against acyclovir-sensitive and acyclovir-resistant HSV type 1 strains was examined. The cytotoxic effect of a phytochemically defined birch bark triterpene extract (TE) as well as different pentacyclic triterpenes was analyzed in cell culture, and revealed a moderate cytotoxicity on RC-37 cells. TE, betulin, lupeol and betulinic acid exhibited high levels of antiviral activity against HSV-1 in viral suspension tests with IC50 values ranging between 0.2 and 0.5μg/ml. Infectivity of acyclovir-sensitive and clinical isolates of acyclovir-resistant HSV-1 strains was significantly reduced by all tested compounds and a direct concentration- and time-dependent antiherpetic activity could be demonstrated. In order to determine the mode of antiviral action, TE and the compounds were added at different times during the viral infection cycle. Addition of these drugs to uninfected cells prior to infection or to herpesvirus-infected cells during intracellular replication had low effect on virus multiplication. Minor virucidal activity of triterpenes was observed, however both TE and tested compounds exhibited high anti-herpetic activity when viruses were pretreated with these drugs prior to infection. Pentacyclic triterpenes inhibit acyclovir-sensitive and acyclovir-resistant clinical isolates of HSV-1 in the early phase of infection.